2002
DOI: 10.1103/physrevb.66.045308
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-correlated photon pairs from a single quantum dot

Abstract: Polarization correlation in a linear basis, but not entanglement, is observed between the biexciton and single-exciton photons emitted by a single InAs quantum dot in a two-photon cascade. The results are well described quantitatively by a probabilistic model that includes two decay paths for a biexciton through a non-degenerate pair of one-exciton states, with the polarization of the emitted photons depending on the decay path. The results show that spin non-degeneracy due to quantumdot asymmetry is a signifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
181
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(192 citation statements)
references
References 29 publications
9
181
1
1
Order By: Relevance
“…However, polarized cross-correlation measurements on the exciton and biexciton photons have confirmed that a splitting of the intermediate exciton state results in spectral "which path" information, and the emission of only polarization-correlated photon pairs. [12][13][14] In this Brief Report we present the reduction of this exciton level splitting through the zero point, a crucial step toward the generation of entangled photon pairs. The splitting of the exciton level has been measured in many dot systems including InAs/ GaAs, 12 CdSe/ ZnSe, 15 InP/ GaInP, 16 and interface fluctuations in thin GaAs/ AlGaAs quantum wells.…”
mentioning
confidence: 99%
“…However, polarized cross-correlation measurements on the exciton and biexciton photons have confirmed that a splitting of the intermediate exciton state results in spectral "which path" information, and the emission of only polarization-correlated photon pairs. [12][13][14] In this Brief Report we present the reduction of this exciton level splitting through the zero point, a crucial step toward the generation of entangled photon pairs. The splitting of the exciton level has been measured in many dot systems including InAs/ GaAs, 12 CdSe/ ZnSe, 15 InP/ GaInP, 16 and interface fluctuations in thin GaAs/ AlGaAs quantum wells.…”
mentioning
confidence: 99%
“…The experimental realization of Rabi rotations between the biexciton state and an exciton state [165], as well as between the biexciton and the ground state [149,150,18,151,166,167], which can be both described in the four-level model, has great potential impact on the field of quantum logic where exciton-biexciton systems have been proposed as two-qubit quantum gates [21,165] or as emitters of entangled photon pairs [11,12,13,14,15,16,17,18]. Rabi rotations between the ground and the biexciton state were also preformed by using two-color excitations [168].…”
Section: Rabi Rotationsmentioning
confidence: 99%
“…This compatibility with existing technologies makes QDs attractive candidates for a wide range of applications ranging from optoelectronic devices like QD lasers [1,2,3,4], where the target is an improved performance compared to other laser structures, up to new applications in the fields of quantum cryptography or quantum information processing, where the presence of discrete energy levels is mandatory. Examples of such quantum applications are single-photon sources [5,6,7,8,9,10], sources of entangled photon pairs [11,12,13,14,15,16,17,18], and qubit devices or quantum gates [19,20,21,22,23,24]. The functionality of all these latter applications relies on the preparation of a well-defined quantum state.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, suppression of spin flip during whole processes including absorption, capture, relaxation, and radiative recombination is a crucial issue. In case of neutral exciton, long-range electron-hole exchange interaction stems from an anisotropic confinement potential [3][4][5] will lead to a simultaneous spin flip of electron and hole [6]. Singly-charged exciton (trion), on the other hand, is free from the exchange interaction owing to the presence of spin-paired carriers.…”
Section: Introductionmentioning
confidence: 99%